Slab Horizontal Subduction and Slab Tearing Beneath East Asia - Ma, Pengfei; Liu, Shaofeng; Gurnis, Michael; Zhang, Bo (Geophysical research letters, 2019)
The present‐day architecture of subducted slabs in the mantle as inferred from seismic tomography is a record of plate tectonics through geological time. The unusually large slab that lies nearly horizontally above the 660‐km mantle discontinuity beneath East Asia is presumably from subduction of the Pacific plate. Numerical models have been used to explore the mechanical and geophysical factors that contribute to slab stagnation, but the evolution of this horizontal structure is not fully understood because of uncertainties in the plate‐tectonic history and mantle heterogeneity. Here we show that forward mantle‐flow models constrained by updated tectonic reconstructions can essentially fit major features in the seismic tomography beneath East Asia. Specifically, significant tearing propagated through the subducted western Pacific slab as the Philippine Sea plate rotated clockwise during the Miocene, leading to internal slab segmentation. We believe this tearing associated with Philippine Sea plate rotation also affects the horizontal configuration of slabs. Plain Language Summary The present‐day architecture of subducted slabs in the mantle as inferred from seismic tomography is a record of plate tectonics through geological time. The structure of the mantle below East Asia is dominated by a flat slab which extends more than 2,300 km laterally inland (Liu, Zhao, et al., 2017, https://doi.org/10.1016/j.epsl.2017.02.024, https://doi.org/10.1016/j.earscirev.2017.10.012). The origin of this unusual but globally significant flat‐slab structure has been the subject of considerable discussion in the literature through a series of global and high‐resolution seismic inversions. Is this phenomenon caused by unusual regional processes, or have some global mantle processes been overlooked? Here we reproduce this highly unusual flat‐slab structure with a four‐dimensional computational model and argue that this slab is a natural consequence of the plate‐tectonic evolution of East Asia. We provide a solution to this problem through a combination of new plate‐tectonic reconstructions and a 4‐D computational approach that assimilates plate tectonics with the physics of mantle convection. This paper reports a new paradigm for the East Asia margin, where the regional tectonics are characterized by the development of a typical trench‐trench‐trench triple junction, and resultant significant tearing that propagated through the subducted western Pacific slab as the Philippine Sea plate rotated clockwise during the Miocene. Key Points A new plate reconstruction of East Asia fully depicts the NE migration of a trench‐trench‐trench triple junction since 30 Ma This triple‐junction migration led to the overlapping, tearing, and detachment of subducted slabs in East Asia Large–scale ambient mantle flow should have contributed to the formation of the horizontal slab